Perilaku Psikopat Tokoh Seiichi Kirishima Dalam Komik HIDEOUT Karya Masasumi Kakizaki - Faris Maulana, Hasani; Andry Anita Dewi, Ni Made; Damayanti, Silvia (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p08, 2018)
This research, entitled “Seiichi Kirishima’s Psychopath Behaviors in HIDEOUT Comic by Masasumi Kakizaki”, analyzed Seiichi Kirishima’s characters and factors that cause Seiichi Kirishima become a pshychopath in a comic entitled HIDEOUT. This research used literature psychology theory by Wellek and Warren, pshycho analysis theory by Sigmund Freud, pshychopaty theory by Hare, pshychopath classify theory by Chekley, and semiotic theory by Marcel Danesi. The result of this research is Seiichi Kirishima included to the primary pshychopath category. Seiichi Kirishima’s psychopath behaviors are anti social, egocentric, lacks of affraid, cruel, often lying, and has serious problem from his past. There are internal and external factors of his psychopath behaviors.  The internal factor is unbalances in Seiichi Kirishima’s personal structure and the external factors for the example there are unsuccesfully in his job and his son was dead.